Peningkatan Pemahaman Siswa pada Materi Klasifikasi Makhluk Hidup melalui Model Cooperative Learning Tipe Jigsaw di MTs Negeri 8 Kebumen - Akbar, Arif Hidayat (Discovery, 2024)
The aim of this research was to determine the application of the Jigsaw type Cooperative Learning model in improving the understanding and learning outcomes of science in the Classification of Living Creatures material for student’s MTs Negeri 8 Kebumen. Researcher used Classroom Action Research (PTK) with descriptive analysis techniques. This analysis was used before and after implementing the Cooperative Learning learning model. The research results showed that in the daily assessment after implementing this learning model, the average student learning outcome was 86.84 with learning completeness of 91.43%. It showed significantly improved results. In conditions before implementing this learning model, the average student learning outcome was 66.75 with learning completeness of 20.00%. It means that the application of the Jigsaw type Cooperative Learning learning model to the Classification of Living Creatures material could improve student learning outcomes in Negeri 8 Kebumen.